Optimisation of Microwave, Ultrasonic and Combined Microwave-Ultrasonic Pretreatment Conditions for Enhanced Anaerobic Digestion - Yeneneh, Anteneh; Sen, Tushar; Ang, H.; Kayaalp, A. (Springer, 2017)
This study describes the effect of microwave and low-frequency ultrasonic pretreatment power intensity, time and density on thickened excess activated sludge (TEAS) characteristics and anaerobic digester performance. Key parameters affecting the efficiency of ultrasonic and microwave pretreatment were identified and optimised. The effect of change in ultrasonication and microwave pretreatment conditions on sludge degradation and other characteristics were analysed. Ultrasonication power, density and time were important factors in the sludge solubilisation process. Microwave density and pretreatment time also influenced solubilisation of TEAS, and the effects were investigated for treatment densities of 3.2, 4.6 and 6.4 W/ml and treatment duration of 1–7 min. Higher sludge degradability, higher volatile solid removal and better digester performance were achieved for anaerobic digestion with lower ultrasonication power of 80 W, ultrasonication time of 6 min, and ultrasonic density of 0.32 W/ml. The volume of biogas produced and kinetics, dewaterability of digested sludge, COD reduction and other sludge properties were optimised for the aforementioned ultrasonication and microwave pretreatment conditions for TEAS. It was observed that sludge dewaterability deteriorated with increasing sonication power density and sludge solubilisation. Hence, the balance between sludge dewaterability and solubilisation should be maintained for optimum performance. Thus, the selection of ultrasonic pretreatment time and power is a trade-off between sludge solubilisation and dewaterability.